Mobilizing Resources but Still Mining for Opportunities?: Indigenous Peoples, their Land and the Philippine State - VILLANUEVA, PRINCE AIAN G.; RUANTO, ANFERNEE P (Universitas Muhammadiyah Yogyakarta, 2016)
The Kalipunan ng mga Katutubong Mamamayan ng Pilipinas (KAMP) or theNational Alliance of Indigenous Peoples’ Organization in the Philippines is almost in their 30 years of existence and yet, like in most cases of indigenouspeoples’ issues, there is still no significant number of studies about their role incampaigning for the betterment of the Indigenous Cultural Communities. Anchored on political opportunity structures theory as a guide, the basic motivation of the paper is to illustrate how the KAMP fights and survives through resource mobilization and how the government – represented by National Commission on Indigenous Peoples (NCIP) and Department of Environment and Natural Resources (DENR) accommodate their interests. Using archival research, secondary data analysis, elite interview and participant observation, the paper asserts that KAMP’s use of their organizational structure, advocacy campaigns and political assaults as their basic resources to fight for the Nueva Vizcaya Mining issue are relatively insufficient to a centralist and relatively closed government, despite the presence of democratic institutions. The ability of the Philippine government to strike the balance between development and indigenous peoples’ rights protection shall remain to be a defining feature if not a challenge to the quality of democracy and governance in our land.